Techno-economic analysis of palm oil mill wastes to generate power for grid-connected utilization - Mahlia, T.M.I.; Yong, J.H.; Safari, A.; Mekhilef, Saad (2012)
In association with the rapidly depleting fossil fuel reserves as well as the unstable fluctuations of the fuel prices, efforts are focused on exploration of an alternative to replace conventional energy sources especially in the power generation sector. In Malaysia, the palm oil industry produces significant amount of wastes that can be used as an admirable choice for energy production. This study investigates the feasibility and stability of palm oil wastes for power generation including introduction to the palm oil industry as well as the wastes generated, the assessment of the supply, current demand and the future trend of biomass energy in Malaysia. Furthermore, economic aspects of the biomass power generation are discussed in term of the payback period. Equations which are used to calculate the potential of power generation from palm oil are also presented and assessments were conducted based on the available information and models. It was confirmed that palm oil wastes are one of the promising candidates for biomass power generation for grid connected in Malaysia; however, further study is necessary to identify the technologies available in this area.